The Rhetorical Goddess: A Feminist Perspective on Women in Magic. Issue 1 (December 2014) - Bruns, Laura C.; Zompetti, Joseph P.
Abstract : Although female magicians have existed since the rise of entertainment magic, women have faced difficulty in entering the "fraternity" of the magic community. As an art form largely based around persuasion, it is useful to study the performance of magic as a text. It is additionally useful to study female magicians within this context of rhetoric. Not only will examining the rhetoric of female magicians provide insights on the rhetoric of women in this unique arena, but also of women in a historically gendered and underrepresented field. Research into this area may disclose other details regarding the communicative differences between women and men and how communication is adapted within a gendered communication paradigm.